Desenvolvimento de um sistema microcontrolado de monitoramento e registro de vazão de água - Biffi, Rodrigo Bianchini (2020)
The objective of this paper was the development of a miconcontrolled equipment capable of monitoring and registering water flow in a closed circuit, to be used in the analysis of the mould cooling process for plastic injection and blow. by using a Hall effect turbine flowmeter, it guarantees a larger lifespan and a decreased maintenance cost, if compared to analogic rotameters currently installed in injector machinery. In order to analyze its efficiency, a data logger was incorporated to the system, allowing the comparison of recorded data over time in a reduced scale model of water flow, using a water pump, a water tank and hoses. The results’ standard deviation was small enough to assume a good precision on the sensor.